Interface-Targeting Strategy Enables Two-Photon Fluorescent Lipid Droplet Probes for High-Fidelity Imaging of Turbid Tissues and Detecting Fatty Liver - Guo, Lifang; Tian, Minggang; Feng, Ruiqing; Zhang, Ge; Zhang, Ruoyao; Li, Xuechen; Liu, Zhiqiang; He, Xiuquan; Sun, Jing Zhi; Yu, Xiaoqiang (ACS applied materials & interfaces, 2018)
Lipid droplets (LDs) with unique interfacial architecture not only play crucial roles in protecting a cell from lipotoxicity and lipoapoptosis but also closely relate with many diseases such as fatty liver and diabetes. Thus, as one of the important applied biomaterials, fluorescent probes with ultrahigh selectivity for in situ and high-fidelity imaging of LDs in living cells and tissues are critical to elucidate relevant physiological and pathological events as well as detect related diseases. However, available probes only utilizing LDs’ waterless neutral cores but ignoring the unique phospholipid monolayer interfaces exhibit low selectivity. They cannot differentiate neutral cores of LDs from intracellular other lipophilic microenvironments, which results in extensively cloud-like background noise and severely limited their bioapplications. Herein, to design LD probes with ultrahigh selectivity, the exceptional interfacial architecture of LDs is considered adequately and thus an interface-targeting strategy is proposed for the first time. According to the novel strategy, we have developed two amphipathic fluorescent probes (N-Cy and N-Py) by introducing different cations into a lipophilic fluorophore (nitrobenzoxadiazole (NBD)). Consequently, their cationic moiety precisely locates the interfaces through electrostatic interaction and simultaneously NBD entirely embeds into the waterless core via hydrophobic interaction. Thus, high-fidelity and background-free fluorescence imaging of LDs are expectably realized in living cells in situ. Moreover, LDs in turbid tissues like skeletal muscle slices have been clearly imaged (up to 82 μm depth) by a two-photon microscope. Importantly, using N-Cy, we not only intuitively monitored the variations of LDs in number, size, and morphology but also clearly revealed their abnormity in hepatic tissues resulting from fatty liver. Therefore, these unique probes provide excellent imaging tools for elucidating LD-related physiological and pathological processes and the interface-targeting strategy possesses universal significance for designing probes with ultrahigh selectivity.